1985
DOI: 10.1017/s0022029900024018
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of West African soft cheese by chemical treatment

Abstract: SUMMARYThe effects of sorbic and propionic acids on shelf life and organoleptic characteristics of West African soft cheese stored at 7–9 °C were investigated. In cheeses treated with 0·1% sorbic acid spoilage was delayed and microbial growth, especially mesophilic bacteria, yeasts and moulds, was suppressed compared with untreated controls. Treatment with 0·05% sorbic acid or up to 10% propionic acid was less effective. An objectionable bitter flavour was reported for sorbate-treated cheese but other qualitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 4 publications
0
24
0
2
Order By: Relevance
“…A lot of research has gone into the improvement of its shelf life by using different preservatives. (Aworh & Egounlety, 1985;Anon, 1995). The use of 0.8% propionic acid and 0.8% sodium benzoate in the preservation of cheese for 8 days have been reported by Joseph and Akinyosoye (1997).…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has gone into the improvement of its shelf life by using different preservatives. (Aworh & Egounlety, 1985;Anon, 1995). The use of 0.8% propionic acid and 0.8% sodium benzoate in the preservation of cheese for 8 days have been reported by Joseph and Akinyosoye (1997).…”
Section: Introductionmentioning
confidence: 99%
“…The cheese is usually deep fried in vegetable oil near the end of its shelf life in order to further preserve the cheese. Due to the lack of household refrigeration facilities in Nigeria and West Africa, attempts have been made in the recent past to include starter cultures or various chemical preservatives such as propionic acid, sodium benzoate, and sorbic acid in the production of wara (Anonymous, 1995;Aworh & Egounlety, 1985;Belewu et al, 2005;Joseph & Akinyosoye, 1997;Sanni & Onilude, 1999). Some of these preservatives have been shown to be effective in inhibiting mesophilic and psychrotrophic bacteria as well as coliforms.…”
Section: Introductionmentioning
confidence: 99%
“…[5] There are many research reports presented in the literature on sorbate treatment of cheese. [6][7][8][9][10] Liewen and Marth [6] and Yousef and Marth [7] reported that Aspergillus spp., A. paraciticus, and Penicillium camambertii were inhibited by 500 ppm concentration of sorbate in cheddar cheese. The potassium sorbate inhibited the moulds for 6 months in Kashar cheese.…”
Section: Introductionmentioning
confidence: 99%